"Balance as a way of lifework": early career choices among Israeli senior teacher educators. Issue 1 (2nd January 2022) - Gutman, Mary
ABSTRACT: This study seeks to explore Israeli senior teacher educators' retrospective interpretations of their early career experiences while addressing a special emphasis on cultural and contextual characteristics of the academic colleges of education (ACEs). In order to study in depth the attraction factors of career choices among teacher educators, who have outstanding academic skills and background in university teaching, 10 semi-structured interviews were conducted. The findings pointed to the 'balancing between different fields of work' as a major attraction in choosing both the profession and the academic home among teacher educators. Moreover, three balancing points of utmost importance in career choices are identified as significant: a balance between theory and practice toward educational change; a balance between self-worth and production-based worth; and a balance between social relevance and professional networks. The study concludes with a handful of recommendations for ACE administrators on the strategies of recruiting and retaining new teacher educators with impressive academic achievement.